A novel optical orthogonality control approach based on noise propagation and its application in spin-exchange relaxation-free co-magnetometers - Qin, Bodong; Fan, Wenfeng; Wang, Zhuo; Wang, Ruigang; Xia, Hao; Li, Feng; Liu, Zehua; Quan, Wei (Measurement : journal of the International Measurement Confederation, 2025)
This paper presents a non-destructive optical orthogonality control method based on adaptive gradient descent for spin-exchange relaxation-free co-magnetometers (SERFCM). The spin-exchange optical pumping technique serves as the foundation of SERFCM measurement. Analyzing the impact of pump power fluctuation on the transverse polarizability of alkali metal atoms in the presence of non-orthogonal beams, considering stochastic noise propagation, is addressed. Subsequently, an optical orthogonal calibration scheme is proposed. Leveraging the proposed orthogonal calibration scheme, an adaptive gradient descent method based on the reference model is formulated, and simulation validates its effectiveness in addressing the rapid online optimization control of SERFCM optical quadrature. Experimental results indicate that the proposed optical orthogonal calibration scheme offers higher accuracy, with the proposed optical orthogonal control algorithm saving 34% of the time compared to the traditional algorithm. Finally, the stability of SERFCM is evaluated using Allan variance, demonstrating that the adjusted SERFCM enhances short-term stability by 84% at around 1s and long-term stability by 639% at around 300s. •Optical calibration method reduces SERFCM noise, ensuring precise orthogonality.•Adaptive gradient descent algorithm cuts calibration time by 34% over traditional methods.•Enhances long-term stability, applicable to a range of atomic sensors.